DETERMINATION OF HOTEL PARKING NEEDS IN BANDUNG BASED ON SPATIAL CONDITION WITH SUPPLY-DEMAND APPROACH - TIARDI - Nim: 15414043, KHAIRANA
Parking is one of important components in urban transportation system because vehicles will not always move. Parking supply will be different due to different spatial conditions and land uses. Parking supply is good if it’s efficient;neither less nor excess. Nowadays, Bandung tourists tend to use their private vehicles that implies to hotel parking supply. The parking standards made by Indonesia’s General Directorate of Land Transportation in 1996 do not consider any spatial conditions. This research will model hotel parking space needs in Bandung based on different spatial conditions. The approach used in this study is supply-demand approach. The methods of analysis used in this study are content, descriptive, regression, and ratio. Content analysis is used to identify factors that affect hotel parking demand. Descriptive analysis is used to describe hotel parking supply and demand in present along with the supply evaluation. Regression and ratio method are used to formulate models that determine parking space needs. This research outcome will show that the parking standards made by Indonesia’s General Directorate of Land Transportation in 1996 is no longer relevant to be applied. This research formed parking models for hotels in general, hotels in congestion area, and hotels in TOD area. Hotels in general should provide 14 parking lots per 100-person-capacity multi purpose room. Hotels in congestion area should provide 5 parking lots per 1.000 m2gross floor area. Hotels in TOD area should provide 7 parking lots in addition of 5 parking lots per 1.000 m2gross floor area and reduction of 1 parking lot per Rp100.000,00 hotel tariff.